DEVELOPMENT OF LEARNING INSTRUMENTS BASED ON RME MODELS TO IMPROVE STUDENTS' MATHEMATICAL LITERACY AND LEARNING INTEREST - Nazri Maulana Khani Selian; Mulyono Mulyono; Mariani Mariani (Universitas Muhammadiyah Prof Dr HAMKA, 2023)
This study employed GeoGebra to develop interactive learning instruments for SLETV content, using the 4-D Thiagaradjan model as the framework, involving four phases: define, design, develop, and disseminate. The investigation included two eighth-grade math teachers and fourteen-year-old eighth-graders, and observational data were collected through needs analysis, interviews, and questionnaires. The data collection comprised need analysis, interviews, and surveys. Before trial implementation, three crucial development requirements had to be met: validity, practicality, and efficacy. The validation of learning instrument formats, illustrations, language, and content showed valid. The research findings indicate that the developed learning instruments were effective, with an average student score of 74.3 on the pretest and 87 on the posttest (meeting the minimum criteria of mastery learning). Teacher's ability to manage learning was rated as very good, with an average score of 4.4. The observation of learning implementation showed an average score of 4.4 in the very good category (practical). The learning instruments based on RME can be used to enhance students' mathematical literacy and learning interest.